1996
DOI: 10.5694/j.1326-5377.1996.tb101352.x
|View full text |Cite
|
Sign up to set email alerts
|

The emergence ofMycobacterium ulceransinfection near Melbourne

Abstract: Objective: To document the emergence of new foci of Mycobacterium ulcerans infection (Bairnsdale ulcer) in Victoria. Methods: From data kept by one of us (J A H) and records from the Mycobacterium Reference Laboratory, Fairfield Hospital, we reviewed cases of M. ulcerans infection in Victoria between 1980 and 1995, and identified those apparently acquired outside the east Gippsland endemic region. A case was defined as a person with a lesion suggestive of M. ulcerans infection, from which the organism had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 10 publications
1
56
0
Order By: Relevance
“…The disease is also endemic in several other countries outside Africa, including rural areas of Papua New Guinea, Malaysia, French Guiana, and Mexico (Figure 1). In Australia, the disease remains uncommon, but there have been increases in both incidence and the number of endemic areas in the last 15 years [13,14]. …”
Section: History and Epidemiologymentioning
confidence: 99%
“…The disease is also endemic in several other countries outside Africa, including rural areas of Papua New Guinea, Malaysia, French Guiana, and Mexico (Figure 1). In Australia, the disease remains uncommon, but there have been increases in both incidence and the number of endemic areas in the last 15 years [13,14]. …”
Section: History and Epidemiologymentioning
confidence: 99%
“…Human BU incidence in south-eastern Australia is on the increase, particularly in the last two decades [2], [8]. The progressive extension of the westernmost extremity of the endemic area from the original Bairnsdale region more than 260 km to the east, and the frequent emergence of new endemic foci are current public health concerns.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that new endemic areas emerge in areas adjacent to recent soil disturbance and flooding [7]. In south-east Australia, infection is consistently associated with coastal areas [8], [9] and the mechanism of transmission remains elusive, although several studies have indicated that mosquitoes may have a role [2], [10]. The bacterium infects a wide range of terrestrial mammals in Australia, including both domestic animals [11][13] and native wildlife [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cases have been reported from at least 32 countries, in regions including Africa, Australia, Southeast Asia, China, Central and South America and the Western Pacific [5]. In Victoria, cases have been reported in Gippsland, Phillip Island [6] and the Mornington [7] and Bellarine Peninsulas [8] [9] [10]. In Queensland there is a significant established focus in Far North Queensland [11] [12].…”
Section: Introductionmentioning
confidence: 99%